O BLOG CORPORATIVO COMO DESAFIO PARA OS PROFISSIONAIS DE COMUNICAÇÃO - Araujo, Clenio (2012)
The desired characteristics for a corporate blog efficiently from the standpoint of communication are the subject of this dissertation. We tried to understand them as well as list them, to verify the applicability of these characteristics and gains relating to the public image of a company through the tool. The methodology used was the study of multiple cases, with analysis of five blogs that contain most of the skills suggested in the evaluation protocol constructed from readings, interviews and visits to blogs. Each blog has studied different strengths, but also improvements that need to be considered. Behaviors of total openness and transparency are even more dialogue discourses practices in organizations that need to take better advantage of opportunities that social media relationship brought.